Understanding the child-doctor relationship in research participation: a qualitative study - Malou L. Luchtenberg; Els L. M. Maeckelberghe; Louise Locock; A. A. Eduard Verhagen (BMC, 2020)
Abstract Background Children have reported that one reason for participating in research is to help their doctor. This is potentially harmful if associated with coercive consent but might be beneficial for recruitment. We aimed to explore children's perceptions of the child-doctor relationship in research. Methods This is a multicenter qualitative study with semi structured interviews performed between 2010 and 2011 (United Kingdom) and 2017-2019 (the Netherlands). Interviews took place nationwide at children's homes. We performed a secondary analysis of the two datasets, combining an amplified analysis aimed to enlarge our dataset, and a supplementary analysis, which is a more in-depth investigation of emergent themes that were not fully addressed in the original studies. All participants had been involved in decisions about research participation, either as healthy volunteers, or as patients. Recruitment was aimed for a purposive maximum variation sample, and continued until data saturation occurred. We have studied how children perceived the child-doctor relationship in research. Interviews were audiotaped or videotaped, transcribed verbatim, and thematically analyzed using Atlas.ti software. Results In total, 52 children were recruited aged 9 to 18, 29 in the United Kingdom and 23 in the Netherlands. Children's decision-making depended strongly on support by research professionals, both in giving consent and during participation. Often, their treating physician was involved in the research process. Familiarity and trust were important and related to the extent to which children thought doctors understood their situation, were medically competent, showed support and care, and gave priority to the individual child's safety. A trusting relationship led to a feeling of mutuality and enhanced children's confidence. This resulted in improving their experiences throughout the entire research process. None of the participants reported that they felt compelled to participate in the research. Conclusions The child-doctor relationship in pediatric research should be characterized by familiarity and trust. This does not compromise children's voluntary decision but enhances children's confidence and might result in a feeling of mutuality. By addressing the participation of children as an iterative process during which treatment and research go hand in hand, the recruitment and participation of children in research can be improved.